Shaping participation: an international NGO implementing a government participation policy. Issue 8 (17th November 2017) - Gilfillan, Beth; Fee, Anthony
ABSTRACT: This article reports on a case study of how one NGO utilised a government participation policy to establish ostensibly participatory spaces in the Cambodian health sector. The ethnographic field study revealed how the NGO exerted influence in establishing and facilitating participative committees by controlling membership, resources, and meeting agendas. This resulted in limited citizen participation, with committees used to educate, lobby, and mobilise community leaders to work towards the NGO's priorities rather than community identified needs. This case contributes to our understanding of insisted spaces and the role of third parties implementing government participation policies.